2005
DOI: 10.1242/jcs.02524
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ARFRP1 (ADP-ribosylation factor-related protein 1) in post-Golgi membrane trafficking

Abstract: ADP-ribosylation factor (ARF)-related protein 1 (ARFRP1) is a small GTPase with significant similarity to the ARF family. However, little is known about the function of ARFRP1 in mammalian cells, although knockout mice of its gene are embryonic lethal. In the present study, we demonstrate that ARFRP1 is associated mainly with the trans-Golgi compartment and the trans-Golgi network (TGN) and is an essential regulatory factor for targeting of Arl1 and GRIP domain-containing proteins, golgin-97 and golgin-245, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 57 publications
5
72
0
2
Order By: Relevance
“…Based on data in vitro data from cultured cells transfected with ARFRP1 constructs, we and others have previously suggested that the GTPase is required for targeting of ARL1 and of its effector Golgin-245 to the trans-Golgi network (7)(8)(9)(10)43). The present data provide solid proof for this conclusion in showing that ARL1 dissociated from Golgi membranes to the cytosol in an in vivo knockdown of Arfrp1 (Arfrp1 vilϪ/Ϫ epithelial cells, Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Based on data in vitro data from cultured cells transfected with ARFRP1 constructs, we and others have previously suggested that the GTPase is required for targeting of ARL1 and of its effector Golgin-245 to the trans-Golgi network (7)(8)(9)(10)43). The present data provide solid proof for this conclusion in showing that ARL1 dissociated from Golgi membranes to the cytosol in an in vivo knockdown of Arfrp1 (Arfrp1 vilϪ/Ϫ epithelial cells, Fig.…”
Section: Discussionsupporting
confidence: 82%
“…We and others have recently shown that ARFRP1 as well as its yeast ortholog Arl3p specifically control targeting of ARL1 and its effector Golgin-245 to the trans-Golgi (7)(8)(9)(10). GTPbound ARFRP1 (ARFRP1-Q79L mutant) was associated with Golgi membranes and colocalized with ARL1.…”
mentioning
confidence: 99%
“…Cell Culture, siRNA-mediated Knockdown, and Immunofluorescence Analysis-Culture of HeLa cells and transfection of expression plasmids were performed as described previously (29,30). RPE1 cells were grown in a 1:1 mixture of Dulbecco's modified Eagle's medium and Ham's F-12 medium supplemented with 10% heat-inactivated fetal calf serum, 2 mM L-glutamine, 100 units/ml penicillin, and 100 g/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Culture of HeLa cells and transfection of expression plasmids were performed as described previously (Shin et al, 2005. HeLa cell lines stably expressing TfnR-EGFP were established as described previously .…”
Section: Antibodies and Reagentsmentioning
confidence: 99%